Systematic review of patient-reported measures of treatment burden in stroke. Issue 9 (18th September 2019) - Gallacher, Katie I; Quinn, Terry; Kidd, Lisa; Eton, David; Dillon, Megan; Elliot, Jennifer; Johnston, Natalie; Erwin, Patricia J; Mair, Frances
Abstract : Objectives: Treatment burden is the workload of healthcare for people with long-term conditions (LTC) and its impact on well-being. A method of measurement is required to identify those experiencing high burden and to measure intervention efficacy. Our aim was to identify, examine and appraise validated patient-reported measures (PRMs) of treatment burden in stroke. Here, stroke serves as an exemplar LTC of older adults. Design: A systematic review of published studies that describe the development and validation of PRMs measuring treatment burden in stroke survivors. Data sources: We searched MEDLINE, Embase, CINAHL and PsycINFO electronic databases. Eligibility criteria: Studies published between January 2000 and 12 April 2019 inclusive, in English language. No restrictions were set based on clinical setting or geographical location. Data extraction and synthesis: Screening, data extraction and quality appraisal were conducted by two independent reviewers. Content of the PRMs was compared with a published taxonomy of treatment burden. Quality appraisal was conducted using International Society for Quality of Life Research standards. Results: From 3993 articles, 6 relevant PRMs were identified: 3 were stroke specific: The Satisfaction with Stroke Care questionnaire; The Stroke Patient-Reported Outcome Measure and The Barriers to Physical Activity after Stroke scale. Three were generic but validated in stroke: The WHO Quality of Life-100; The Patient's Questionnaire on Participation in Discharge Planning and The Chao Perception of Continuity scale. None comprehensively measured treatment burden. Examples of omitted burdens included developing coping strategies, managing finances and returning to driving. The most notable issue regarding quality appraisal was that three PRMs lacked any underpinning qualitative research relevant to the sample. Conclusion: There is a need to develop a comprehensive PRM of treatment burden for use in stroke, with potential for use in other older populations.